A framework for value investing. (December 2013) - Chee, Seungmin; Sloan, Richard; Uysal, Aydin
This paper provides a framework for defining, formulating and evaluating value investment strategies. We define the relative value of an investment in terms of the prospective yield implied by the investment's current price and expected future cash flows. We develop an intuitive and parsimonious approach for estimating the prospective yield by aggregating cum-dividend expected earnings over a suitable forecast horizon. We also adapt this approach to construct a realized yield metric that can be used as a more direct alternative to realized security returns in evaluating value strategies. We illustrate how our framework can be used to evaluate existing measures of value, construct improved measures of value, and attribute the returns to an investment strategy to value versus other sources.